2013
DOI: 10.1002/ange.201306881
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of the Cycloparaphenylene Radical Cation and Dication

Abstract: Scheme 1. Synthesis of the radical cation and dication of [8]CPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The calculations also suggest that the radical cations have a more quinoidal contribution than the neutral compounds, judging from the BLA values of the paraphenylene units. The same trend was also observed for CPP [42] …”
Section: Resultssupporting
confidence: 83%
“…The calculations also suggest that the radical cations have a more quinoidal contribution than the neutral compounds, judging from the BLA values of the paraphenylene units. The same trend was also observed for CPP [42] …”
Section: Resultssupporting
confidence: 83%
“…They have gained significant attention recently ,,,,,. So far systematic studies of [ n ]CPPs have focused on their size‐dependent properties such as HOMO‐LUMO energy gaps, Raman spectroscopy, photophysical properties,, and redox potentials, and size‐complementary host‐guest chemistry ,,. [ n ]CPPs with their curved conjugated surfaces show great potential for bottom‐up synthesis of nanobelts[ 24 ] and novel donor‐acceptor nanohoop materials .…”
Section: Introductionmentioning
confidence: 99%
“…[10] Among the various properties of CPPs, electronic properties, as exemplified by the redox properties and orbital modulation, are among the most intriguing properties associated with the potential applications of CPPs in nanoelectronic materials. [11] Theoretical studies by Yamago and coworkers indicated that, [5b] in sharp contrast to linear oligoparaphenylenes, the HOMO-LUMO energy gap of CPPs becomes narrower as the number of phenylene rings decreases, because of the increase and decrease in the HOMO and LUMO energies, respectively (HOMO = highest occupied molecular orbital, LUMO = lowest unoccupied molecular orbital). Furthermore, the electrochemical analyses proved the size dependence of the HOMO-LUMO energy gap.…”
mentioning
confidence: 99%